Identifikasi Perilaku Konsumen Terhadap Keputusan Pembelian Kopi di Kedai Kopi - Encep Jianul Hayat; Andri Ikhwana; Sandi Nayoan (Jurnal Kalibrasi, 2022)
In recent years, external cultural influences have influenced the lifestyle of today's society. The existence of outside cultural influences has made people now switch to drinking coffee at coffee shops. Based on this, this research was conducted to identify the factors that influence consumer behavior towards coffee buying decisions in coffee shops and determine coffee shop development strategies. Collecting data in this study used primary data in the form of a questionnaire with a total sample of 100 respondents and was carried out using random. The method used is descriptive analysis and factor analysis. Based on the results of the study, the results obtained were seven factors for the development of the coffee shop business, namely psychological factors, location or place factors, reference group factors, family factors, social media factors, personal factors and the beauty factor of the coffee shop. In order for the coffee shop to develop, the strategies that can be implemented include product quality, strategic location or place, a comfortable place, the best service, using social media as a promotional medium, and good room interiors.